Correlation of bisphenol A and bisphenol S exposure with the metabolic parameters on FDG PET/CT image - Xiao, Liu; Wen, Xue; Li, Lin; Li, Yuhao (Frontiers in Public Health, 2024)
PurposeBisphenol A (BPA) and its analogs have been proved to be harmful to human health. This study aimed to assess the correlation of BPA and its major analog, Bisphenol S (BPS), with metabolic parameters within main organs using 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) imaging.MethodsA retrospective analysis was conducted on patients who had undergone FDG PET/CT imaging and were also examined for BPA and BPS levels. Urine samples were collected for detection of BPA and BPS. Standardized uptake values (SUVmax and SUVmean) of main organ tissues including liver, blood, spleen, muscle, thyroid, and cerebral cortex were quantified. Statistical analysis was performed using Spearman’s rank correlation.ResultsForty patients (20 female, 20 male; mean age: 56.1 ± 15.4 years) were included. Mean urine BPA and BPS concentrations were 2.1 ± 1.2 ng/mL and 1 ± 0.6 ng/mL, respectively. Urine BPA exhibited a moderate positive correlation with liver SUVmax (r = 0.351, p = 0.026) and SUVmean (r = 0.361, p = 0.022) in male. No significant correlations were found between BPA and blood, muscle, spleen, thyroid, and cerebral cortex (p > 0.05). Conversely, urine BPS demonstrated a negative correlation with thyroid SUVmax in male (r = −0.43, p = 0.012) and SUVmean (r = −0.432, p = 0.012), while a positive correlation was observed between BPS and cerebral cortex SUVmax in female (r = 0.366, p = 0.033).ConclusionUrinary levels of BPA and BPS exerted distinct influences on tissue metabolic parameters observed via FDG PET/CT imaging, particularly affecting the liver, thyroid, and cerebral cortex.